A Study on Gender Preference for the Desired Fertility and Factors Influencing Son Preference in Southern India - Marinayakanakoppalu R Ravi; Nagaralu C Ashok (Medsci Publications, 2017)
Introduction: Though the overall sex ratio in India has increased by 0.75% in the last decade, the child sex ratio between 0-6 years age group has dropped to all time low since independence to 914 females against 1000 males. Decreased child sex ratio has been observed in Karnataka including Mysore district in the last decade. Hence a study was considered for the gender preferences for the desired fertility. Objectives: The study conducted to determine the sex preference for desired fertility among eligible couples and also to assess factors influencing child sex ratio. Methodology: Cross sectional study among rural population of Mysore district consisted a total of 402 eligible couples. Data regarding various basic socio‑demographic characteristics & village-level economic development were collected. Results: The study showed that 97.51 % of women want at least one girl child in the family. Majority of women 50.99% had equal preference for of boys and girls. Conclusion: It would be to better understand & work towards finding the motivations and social norms of the women and communities who do not express a son preference.